Peningkatan Kemampuan Menulis Karangan Narasi Dengan Mengunakan Media Gambar Seri - Rismayanti, Noni; Dewi, Resnita; Tanduk, Rita (CV. ITTC INDONESIA, 2024)
The purpose of this research is to determine the use of series image media in improving students' skills and motivation in writing narrative essays and to find out the factors that influence students in writing narrative essays using series image media for class IV SDN 010 Pakasassan Mamasa. The research carried out was classroom action research. Type of quantitative descriptive research. Data collection procedures were carried out using interviews, journals and tests. Data analysis techniques use qualitative and quantitative data analysis techniques. The aim of data analysis techniques is to find out in detail how to obtain data and the development of research results. The results of the research found in this study were the students' completeness in learning Indonesian after applying the series of picture media in cycle I. It was found that 6 students or 24% had successfully completed the ability to write narrative essays. Meanwhile, in cycle II it was found that the highest student score was 95 with a score range of 25 and an average score of 86.01 from a total of 25 students. It can be concluded that the use of series image media has a positive influence on learning to write narrative essays.